Isolation Of Chitosan From Cuttlefish Bones - Ningrum, Siti Rahmi; Sinaga, Siti Morin; Harahap, Urip (International Journal of Science, Technology & Management, 2022)
One of the potential natural resources in Indonesia is the abundance of natural resources in the marine sector. The survey results show that the sale of cuttlefish in the market indicates that the demand for cuttlefish is very high. Cuttlefish is a type of marine animal that is widely consumed by the public because of its very high protein content, but the part used from this cuttlefish is the meat, while the squid bones are discarded. Cuttlefish bone is one of the natural ingredients that contains chitin, and when the isolation process is carried out with the stages of deproteinization, demineralization, and deacetylation, it can produce chitosan compounds. The aim of the study was to isolate chitosan from cuttlefish bones. Isolation of chitosan includes 3 basic stages, namely deproteinization, demineralization, and deacetylation. Then the characteristics of chitosan from cuttlefish bones are analyzed, namely water content analysis, ash content, protein content, ninhydrin test, and FT-IR characteristics. The results of characteristic testing of 8.04% water content, 1.73% ash content, and 4.8% protein content, ninhydrin test results showed that cuttlefish bone chitosan had an amine group, and FT-IR results showed that the absorption bands of C-O and C-N groups. The conclusion of this study shows that chitosan can be isolated from cuttlefish bones.